PENGARUH TIPE NUMBERED HEAD TOGETHER TERHADAP HASIL BELAJAR IPS SISWA KELAS IV SD - Yulianti, Dwi; Marli, Suhardi; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The problem in this research is "How is the influence of the application of Numbered Head Together type to the learning result of Social Science of the fourth grade students of Public Alementary School 21 Pontianak Barat?". This study aims to obtain information about the effect of the implementation of Numbered Head Together on the results of learning Social Sciences of the fourth grade students of Public Alementary School 21 West Pontianak. This research uses experimental type experimental design (quasy experimental design). With the experimental design of Non Equivalent Control Group Design. Population in this research is all fourth grader of State Elementary School of West Pontianak Sub-district including accredited group B of B is 210 students and still use Education Unit Level Curriculum (KTSP). The sample of this research is the students of class IV A (control class) which is 29 students and class IV B (experiment class) which is 30 students. Instruments to measure student learning outcomes in the form of tests with multiple choice form as much as 50 questions. Based on the result of data analysis, the mean of post-test of control class is 60,37 and the average of experimental class post-test is 71,2. The result of hypothesis test using t-test (Saparated varian) is obtained tcount = 0,6954 for dk 57 and Î± = 5% obtained t table equal to 1,995, which means thitung> ttable (0,6954> 1,995), Ha is accepted. So, it can be concluded that there is influence of the application of type Number Head Together on Social Science learning on the results of students of fourth grade of Public Alementary School 21 Pontianak Barat. From the calculation of effect size (ES), obtained ES of 0.83 (zero point eighty three) with high criteria. This means that Numbered Head Together has a high effect on students' learning outcomes on materials that recognize natural resources, economic activities, and technological advances in regencies / cities and provinces in the fourth grade of Pontianak West Elementary School.Â Keyword : Influence, Numbered Head Together, Learning outcomes